Religious, Cultural and Legal Barriers to Organ Donation: The Case of Bangladesh - Farid, Md Shaikh; Naim Mou, Tahrima Binta (Bangladesh Journal of Bioethics, 2021)
There is a substantial shortage of organs available for transplantation in Bangladesh. This has resulted in the commodification of organs. This study analyzes the religious, cultural, and legal barriers to organ donation in Bangladesh. It is based on the examination of available literature and primary sources i.e. religious decrees and opinions of religious leaders of faith traditions, and the Bangladesh Organ Donation Act, 1999. The literature was retrieved from databases, such as PubMed, BioMed, and Google Scholar using the key words: organ donation in Islam, organ donation in Bangladesh, organ donation and religions. The study found that although many Islamic scholars accept organ donation, both living and cadaveric, under some conditions, some Bangladeshi Muslim clerics oppose donation. They argue that organ retrieval violates the sanctity of the human body and retrieval of organs may harm a living donor or lead to death, and organ donation may encourage the commercialization of body parts. Both commercialization and harming oneself are considered sins. Thus, the divergent views of Muslim clerics are a major barrier to organ donation among the Bangladeshi Muslims. Cultural and social factors also have a negative impact. Most people desire to be buried with their bodies intact. Although the Bangladesh government promulgated the Bangladesh Organ Donation Act, 1999, and amended it in 2018, it restricted donors and recipients to members of the extended family, which also reduced the donor pool. This study argues that the Muslim Orthodox clerics’ stand against organ donation and other cultural and legal issues are the major obstacles to organ donation in Bangladesh.